Experience as Dr. Jekyll and Mr. Hyde: Performance Outcome Delays in the Private Equity Context. (21st December 2021) - Castellaneta, Francesco; Gottschalg, Oliver; Kacperczyk, Aleksandra; Wright, Mike
Abstract: A large body of work argues that the accumulation of organizational experience fosters learning because firms can correctly modify their understandings on the basis of past actions and their outcomes. But although performance information on past decisions can often be delayed, little research considered how firms respond to experience without complete performance information. In this study, we propose that experience is a double‐edged sword: whereas experience with performance feedback can foster learning, experience without complete performance feedback impedes learning. Using a sample of 7, 223 private equity buyout investments, we find that experience with (in)complete performance information increases (decreases) the performance of a subsequent investment. The positive impact of experience with complete performance information is amplified when firms engage in search, following a shortfall in their performance. Moreover, we find that experience with (in)complete performance information decreases (increases) excessive risk taking. Overall, we advance the experiential learning literature by unpacking the positive and negative impact of experiential learning.